2023
DOI: 10.1038/s41586-022-05640-x
|View full text |Cite|
|
Sign up to set email alerts
|

Stigma receptors control intraspecies and interspecies barriers in Brassicaceae

Abstract: Flowering plants have evolved numerous intraspecific and interspecific prezygotic reproductive barriers to prevent production of unfavourable offspring1. Within a species, self-incompatibility (SI) is a widely utilized mechanism that rejects self-pollen2,3 to avoid inbreeding depression. Interspecific barriers restrain breeding between species and often follow the SI × self-compatible (SC) rule, that is, interspecific pollen is unilaterally incompatible (UI) on SI pistils but unilaterally compatible (UC) on SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 56 publications
1
58
0
Order By: Relevance
“…To test the role wall-sensing receptors play in maintaining cell wall integrity during BR-induced cell expansion, we analyzed how various concentrations of BR affect the growth, morphology, and cell integrity of mutants defective in cell wall-sensing receptor kinases. These include FERONIA (fer-4) (11), HERCULES1(herk1-1) (12), THESEUS1 (the1-1), STRUBBELIG (sub- 21), and MALE DISCOVERER1-INTERACTING RECEPTOR LIKE KINASE 2 (mik2-1) (13). We grew the mutants and wild-type (WT) seedlings on various concentrations (1, 10, 100, 1000 nM) of brassinolide (BL, the most active form of BR) (fig.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the role wall-sensing receptors play in maintaining cell wall integrity during BR-induced cell expansion, we analyzed how various concentrations of BR affect the growth, morphology, and cell integrity of mutants defective in cell wall-sensing receptor kinases. These include FERONIA (fer-4) (11), HERCULES1(herk1-1) (12), THESEUS1 (the1-1), STRUBBELIG (sub- 21), and MALE DISCOVERER1-INTERACTING RECEPTOR LIKE KINASE 2 (mik2-1) (13). We grew the mutants and wild-type (WT) seedlings on various concentrations (1, 10, 100, 1000 nM) of brassinolide (BL, the most active form of BR) (fig.…”
Section: Main Textmentioning
confidence: 99%
“…FER is the most extensively studied member of the malectin domain-containing receptor-like kinase (MLD-RLK) (also known as Catharanthus roseus RLK1-LIKE or CrRLK1L) family. It plays broad and profound roles in diverse processes including sexual reproduction, development of root hair, hormonal responses, mechanic sensing, plant-microbe interactions, and maintaining CWI under abiotic stresses (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Previous studies have shown that BR increases FER RNA level (12).…”
Section: Br Promotes Fer Accumulation At the Plasma Membranementioning
confidence: 99%
“…Two Arabidopsis MAL-L RKs , FERONIA and ANJEA , were also found to function in the stigma as negative regulators of pollen hydration (Liu et al, 2021), and two Arabidopsis LRR RKs , PSKR1 and PSKR2 , are required in the pistil to support pollen tube growth (Stuhrwohldt et al, 2015). Recent studies have found that Arabidopsis pistil factors regulating reproduction, such as LUREs , TICKETs and FERONIA, can not only favour intraspecific pollen tubes, but provide a barrier to closely-related interspecific pollen (Meng et al, 2019; Zhong et al, 2019; Huang et al, 2023). We previously identified predicted Arabidopsis LRR-Malectin ( MAL ) RKs in the LRR VIII-2 RK subgroup (Oelmuller et al, 2023) participating in the earlier stages of pollen-pistil interactions (Lee and Goring, 2021; Bordeleau et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…There are three Brassica SRK interacting proteins that have been shown to function in the Brassica SI pathway: ARM-Repeat-Containing 1 (ARC1; Gu et al ., 1998, Stone et al ., 1999), M Locus Protein Kinase (MLPK; Murase et al ., 2004, Kakita et al ., 2007), and the FERONIA (FER) receptor kinase (Zhang et al ., 2021, Huang et al ., 2023). Brassica napus ARC1 is a Plant U-box (PUB) E3 ubiquitin ligase (Gu et al ., 1998, Azevedo et al ., 2001, Stone et al ., 2003) and was shown to be a key player in the stigma SI pathway through the partial and complete breakdown of SI pollen rejection with RNAi knockdowns and CRISPR/Cas9 mutations, respectively (Stone et al ., 1999, Abhinandan et al ., 2023, Huang et al ., 2023). In the SI pathway, B. napus ARC1 confers pollen rejection by targeting compatibility factors in the stigma for ubiquitination and proteasomal degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of these factors through ARC1 leads to SI pollen rejection by disrupting cellular responses in the stigmatic papillae that are needed for compatible pollen (cellular homeostasis, exocytosis, and membrane remodelling; Abhinandan et al ., 2022). Recently, B. rapa FER was implicated as another signaling branch downstream of SRK (Zhang et al ., 2021, Huang et al ., 2023). It is proposed that SRK interacts with FER which then activates NADPH oxidases causing the accumulation of reactive oxygen species (ROS) to inhibitory levels (Zhang et al ., 2021, Huang et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%